A new monoclinic structure type for ternary gallide MgCoGa2. Issue 6 (6th May 2020) - Pavlyuk, Nazar; Dmytriv, Grygoriy; Pavlyuk, Volodymyr; Rozdzynska-Kielbik, Beata; Nitek, Wojciech; Lasocha, Wieslaw; Chumak, Ihor; Ehrenberg, Helmut
Abstract : The crystal structure of the new monoclinic ternary gallide MgCoGa2 has been determined by the single‐crystal method. The MgCoGa2 structure type represents the structure family based on YPd2 Si and Fe3 C. Abstract : The crystal structure of MgCoGa2 (magnesium cobalt digallide) was solved by direct methods and refined in two space groups as P 21 / c (standard choice) and P 21 / n (non‐standard choice). The refined lattice parameters for the standard choice are a  = 5.1505 (2), b  = 7.2571 (2), c  = 8.0264 (3) Å and β = 125.571 (3)°, and for the non‐standard choice are a  = 5.1505 (2), b  = 7.2571 (2), c  = 6.5464 (2) Å and β = 94.217 (3)°. All parameters for MgCoGa2 refined to R 1  = 0.027 and wR 2  = 0.042 using 594 reflections. The crystal structure peculiarities of this compound are discussed. Particular attention has been given to relationships with other similar structures, such as YPd2 Si and Fe3 C. Crystallographic analysis, together with linear muffin‐tin orbital electronic structure calculations, reveals the presence of three‐dimensional polyatomic nets with partial covalent bonding between the Ga atoms.